Implementasi Data Mining untuk Prediksi Minat Pembelian Produk Roti Menggunakan Metode Apriori pada Toko Roti Dapur Bunda - Ambar Tri Hapsari; Muhamad Muslim Fauzani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to design and develop a web-based stock and sales transaction management system that can help admins manage accounts, stock, transactions, and sales analysis using the Apriori algorithm. This system is designed with main features such as automatic transaction recording, real-time stock monitoring, and customer purchasing pattern analysis reports. The methods used in this study include needs analysis, system design, implementation, and testing using the black box testing method. The test results show that the system runs according to the design and can increase efficiency in managing sales data. However, there are several limitations such as the need for periodic database maintenance and limitations in raw material management. With this system, it is expected that the process of recording transactions and sales analysis can be carried out faster and more accurately, thus helping in making business decisions.